Stereo-Selective Pharmacokinetics of Ilimaquinone Epimers Extracted from a Marine Sponge in Rats - Son, Heebin (Mar Drugs, 2019)
An ilimquinone (IQ) mixture isolated from Hippiospongia metachromia, consisting of IQ and epi-ilimaquinone (epi-IQ), exerts anti-HIV, anti-microbial, anti-inflammatory, and anti-cancer effects. An HPLC-MS/MS method was developed for simultaneous determination of the two epimers in rat plasma, separating them using a biphenyl column. Ascorbic acid is added during the sample preparation to ensure the stability of both isomers. The plasma concentrations of the isomers were monitored following intravenous and oral administration of the IQ mixture in rats as well as the individual epimers that were separately orally administered. Compare to IQ, epi-IQ was much more stable in rat plasma, likely due to its configurations of decalin. Both substances decayed in more than bi-exponential pattern, with an elimination rate constant of 1.2 h(−1) for IQ and 1.7 h(−1) for epi-IQ. The epi-IQ was distributed more widely than IQ by about two-fold. Consequently, the clearance of epi-IQ was greater than that of IQ by about three-fold. The oral absolute bioavailability for IQ was 38%, and, that for epi-IQ, was 13%. Although the systemic exposure of IQ was greater than that of epi-IQ by ~8.7-fold, the clearance of each isomer was similar when administered either orally or intravenously, when normalized for bioavailability. The stereo-specific behavior of the isomers appears to originate from differences in both their tissue distribution and gastrointestinal permeability.